Tal como em um baile de máscaras: o terror de Edgar Allan Poe e João do Rio como um recurso de incentivo à leitura literária em sala de aula - Thadeu Menezes Pinto (2021)
When, while studying the master's degree, I began the conception of a final work focused on a teaching practice, I thought it was good to change, or at least try, the conception formed by my students. I decided to develop a teaching project that focused on reading classic horror tales, soon deciding on the first tale, Edgar Allan Poe's The Masque of Red Death. While discussing my initial ideas with my advisor, he indicated me a second tale, The Baby of Pink Tarlatan, by João do Rio, who resembles the first mainly in relation to a particular aspect: the mask. Unfortunately, due to the extraordinary moment we are in, with in person classes abolished and the detachment limiting the development of a project of this magnitude, the didactic sequence presented here has not yet been applied in any class. The sequence will still be applied and, for me, as a teacher and student, the literary practice in the classroom, as well as the fear caused by the classic and modern horror texts, eternal in the memory of the world, will always be far from their last breath.